Perbedaan Persepsi Tentang Penggunaan Kontrasepsi Implan pada Akseptor Implan dan Non Implan Menggunakan Teori Health Belief Model - Amalia Indah Lestari; Herawati Mansur2; Gita Kostania (Pusat Riset dan Inovasi Nasional, 2025)
Implant is one of the Long-Term Contraceptive Methods (LTCM) that still has relatively low popularity compared to other contraceptive methods. In Indonesia, the use of contraceptive implants remains limited. Data from the 2022 active family planning participants in Malang Regency showed that only 8.2% of acceptors used implants (BPS of East Java Province, 2022). The low coverage may be influenced by various factors, one of which is people’s perception of implants. Perception plays an important role in the process of choosing contraception. Individuals who are able to perceive themselves well tend to have greater self-awareness in selecting a contraceptive method that suits their needs (Windarti, 2020). This phenomenon can be analyzed through the Health Belief Model (HBM), which emphasizes the importance of perception factors such as susceptibility, severity, benefits, and barriers in health-related decision-making, including contraceptive use. This study aims to analyze the differences in perceptions regarding implant contraception based on the Health Belief Model. The research employed a comparative design with a sample of 72 respondents, consisting of 32 implant acceptors and 40 non-implant acceptors, selected using the Proportionate Cluster Random Sampling technique. The research instrument was a structured questionnaire that had been tested for validity and reliability. The results indicated a significant difference in perception of implant use between implant and non-implant acceptors, with a p-value of 0.027 (<0.05). The most meaningful differences were observed in the perceptions of susceptibility and severity. Implant acceptors tended to have a more positive perception of implant contraception, whereas non-implant acceptors were more likely to hold negative perceptions. An individual’s perception becomes positive when it aligns with their needs and, conversely, becomes negative when it conflicts with perceived needs. These findings highlight the importance of strengthening education and counseling on implant contraception to improve community perceptions, thereby encouraging greater use of implants as an effective long-term contraceptive choice.